DEVELOPING AN INVESTMENT STRATEGY IS A KEY TO BOOSTING INVESTMENT ACTIVITY IN THE REGIONS - Omonovich, Tursunov Bekmukhammad; Kholmuminovich, Kholmuminov Aktam (International Journal of Psychosocial Rehabilitation, 2020)
The article is devoted to making proposals for the development of an investment policy strategy by disclosing theoretical and scientific views on the role of investment in economic development, analyzing investments by sources of financing and industries in the regions. It analyzes the state of investments in the manufacturing industry and housing construction, the reproduction structure, changes in sources of financing, as well as the structure of foreign investments and loans by region.